2012
DOI: 10.5455/vetworld.2012.690-693
|View full text |Cite
|
Sign up to set email alerts
|

Nested RT-PCR for ante mortem diagnosis of rabies from body secretionexcretion of animals suspected for rabies

Abstract: Aim: The present study deals with molecular technique Nested RT-PCR for detection of rabies viral RNA from biological fluid samples (Saliva, Milk and Urine) collected from animal suspected for rabies and to compare the sensitivity of Nested RT-PCR applied for ante mortem diagnosis of rabies with conventional technique (immunofluorescence) applied on neural tissue. Molecular technique Materials and Methods: Nested RT-PCR was applied on 62 biological fluid specimens collected from rabies suspected animals. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…27 Rabies virus was detected in 9/24 (37.50%) saliva samples, 2/17 (11.76%) milk samples and 6/21 (28.57%) urine samples. 28 In the present study, humans were exposed to confirmed rabies cattle and buffalo by consuming milk, touching and milking rabid cattle and buffalo, but no human suffered from rabies up to one year of exposure. Moreover, all persons exposed to rabid cattle/buffalo were vaccinated with recommended doses of anti-rabies vaccine.…”
Section: Discussionmentioning
confidence: 71%
“…27 Rabies virus was detected in 9/24 (37.50%) saliva samples, 2/17 (11.76%) milk samples and 6/21 (28.57%) urine samples. 28 In the present study, humans were exposed to confirmed rabies cattle and buffalo by consuming milk, touching and milking rabid cattle and buffalo, but no human suffered from rabies up to one year of exposure. Moreover, all persons exposed to rabid cattle/buffalo were vaccinated with recommended doses of anti-rabies vaccine.…”
Section: Discussionmentioning
confidence: 71%